Translocated Esox lucius L. (PISCES) trigger a Triaenophorus crassus Forel (CESTODA) epidemic in a population of Salvelinus umbla (L.) (PISCES). Issue 3 (25th March 2014) - Schaufler, Gishild; Stögner, Claudia; Achleitner, Daniela; Gassner, Hubert; Žibrat, Uroš; Kaiser, Roland; Schabetsberger, Robert
<x xml:space="preserve">Abstract</x> In 2005, an epidemic of the pike tapeworm Triaenophorus crassus Forel, 1868 broke out in the Arctic charr (Salvelinus umbla (L. 1758)) stock of Lake Grundlsee, Austria. Besides the definitive host Northern pike (Esox lucius L. 1758), which was introduced into the lake in the 1960s, the cestode requires copepods as first and salmonid fish as second intermediate hosts. Within 2 years, the prevalence of the cestode in medium sized Arctic charr increased to almost 100% and the abundance reached a maximum of 55 cysts per fish, leading to the closure of the fishery. Such a massive infection of Arctic charr has never been reported. High pike abundance and the occurrence of a suitable copepod host facilitated the outbreak. The only first intermediate host Cyclops abyssorum praealpinus Kiefer, 1933 predominated the zooplankton community during May, when cestode coracidia hatch from eggs. Only during this infectious period, C. abyssorum praealpinus was eaten by Arctic charr (2–50% of prey organisms). Low fishing pressure on pike enabled the development of a large population that served as reservoir for T. crassus with up to 687 cestodes per fish. To contain the epidemic, 1671 pike were removed between 2008 and 2013. Infection of Arctic charr decreased to 60% and a maximum number of 16 cysts in 2013.